The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jcpp.12773
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and organizational skills problems in ADHD

Abstract: Background: This study tested model-driven predictions regarding working memory's role in the organizational problems associated with ADHD. Method: Children aged 8-13 (M = 10.33, SD = 1.42) with and without ADHD (N = 103; 39 girls; 73% Caucasian/Non-Hispanic) were assessed on multiple, counterbalanced working memory tasks. Parents and teachers completed norm-referenced measures of organizational problems (Children's Organizational Skills Scale; COSS). Results: Results confirmed large magnitude working memory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 77 publications
(170 reference statements)
4
70
3
1
Order By: Relevance
“…Furthermore, the connection between DOSQ’s Assiduity and ASRS’ hyperactivity-impulsivity matches previous findings suggesting that hyperactive symptoms may act to enhance one’s executive functioning (e.g., attention, overall arousal) when engaged in organizational-type activities ( Kofler et al, 2019 ). While hyperactivity (through the mechanism of motor engagement) has been identified as a potential enhancer of general executive functioning ( Kofler et al, 2018 ), this study clarifies that it is specifically assiduity that is particularly enhanced by such hyperactivity-impulsivity symptoms.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Furthermore, the connection between DOSQ’s Assiduity and ASRS’ hyperactivity-impulsivity matches previous findings suggesting that hyperactive symptoms may act to enhance one’s executive functioning (e.g., attention, overall arousal) when engaged in organizational-type activities ( Kofler et al, 2019 ). While hyperactivity (through the mechanism of motor engagement) has been identified as a potential enhancer of general executive functioning ( Kofler et al, 2018 ), this study clarifies that it is specifically assiduity that is particularly enhanced by such hyperactivity-impulsivity symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…The term ‘organizational skills’ refers to a functional set of cognitive abilities which facilitate goal-oriented behaviour ( Clark, Prior & Kinsella, 2002 ). Previous research has identified working memory as a significant causal mechanism for the execution of organizational skills by conceptualizing working memory as both a domain-central executive and general executive function ( Kofler et al, 2011 ; Kofler et al, 2018 ). Despite its multiple conceptualizations, working memory generally refers to the cognitive process of temporary phonological and visuospatial information retention alongside simultaneous processing that is necessary for advanced cognition such as information encoding, learning, reason, and language ( Baddeley, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one article was found investigating time-based prospective memory and the relation to time perception in children with ADHD (Mioni, Santon, executive functions, including time management (Faraone et al, 2015;Shaw et al, 2012). The consequences of time-related deficits in daily life are difficulties in automatizing routines, understanding the concept of time, achieving an overview of time, being on time for an appointment, starting and completing daily activities independently, planning and completing long-term projects, maintain goal-directed actions, understanding and using a calendar, and hurrying up if required (American Psychiatric Association, 2013; Barkley, 1997;Kofler et al, 2018;Langberg, Becker, Epstein, Vaughn, & Girio-Herrera, 2013). This difficulties affects all aspects of life: daily routines and homework, school work, and social relations (American Psychiatric Association, 2013; National Board of Health and Welfare, 2014).…”
Section: Children With Adhd and Time-related Difficulties In Everydaymentioning
confidence: 99%